Dementia Associated with Anticholinergic Drugs Used for Overactive Bladder: A Nested Case-Control Study Using the French National Medical-Administrative Database. Issue 4 (10th October 2022) - Malcher, Marie France; Droupy, Stephane; Berr, Claudine; Ziad, Abdelkrim; Huguet, Helena; Faillie, Jean-Luc; Serrand, Chris; Mura, Thibault
Abstract : Purpose: We analyzed the relationship between use of anticholinergic drugs to treat overactive bladder (OAB) and risk of incident dementia in older patients, overall and for each drug separately. Materials and Methods: We conducted a nested case-control study using the French National Medical-Administrative Database. We identified incident dementia cases and controls from January 1, 2013 to December 31, 2018 in individuals aged ≥60 years. Controls were matched 5:1 to cases by date of case diagnosis (index date), age, sex, and income. We set a 5-year exposure period ending 2 years before the index date (lag-time period to avoid protopathic bias). We quantified cumulative exposure to flavoxate, oxybutynin, solifenacin, trospium, and fesoterodine using defined daily doses (DDDs). We performed conditional logistic regression analyses adjusted for factors known to be associated with OAB and/or dementia including obesity, diabetes, stroke, coronary heart disease, and psychotic disorders. Results: We analyzed 4, 810 cases and 24, 050 matched controls with a median age of 82 years. OAB anticholinergic use was associated with an increased risk of dementia (adjusted OR [aOR]=1.23, 95% CI 1.10–1.37) with a cumulative dose-response: aOR=1.07 (95% CI 0.91–1.25) for 1-90 DDDs, aOR=1.29 (1.05–1.58) for 91–365 DDDs and aOR=1.48 (1.22–1.80) for >365 DDDs. Considering each OAB anticholinergic separately showed a particularly marked increased risk of dementia for oxybutynin and solifenacin, but no increased risk for trospium. Conclusions: When treating OAB in older patients, OAB anticholinergics should be used with caution, taking into account the patient's cognitive status, the anticholinergic load, and the different therapeutic options.